The Role of Family Variables in Fruit and Vegetable Consumption in Pre-School Children - Goldman, Rachel L. (PAGEPress Publications, 2012)
Most Americans, including children, continue to eat fewer fruit and vegetables than is recommended, putting themselves at increased risk of various health conditions. The aim of this study was to evaluate the relative importance of several family environment variables (food availability and accessibility, modelling of food consumption, parenting style, and family mealtime environment) in predicting children’s consumption of fruit and vegetables in a sample of pre-school children from low income, predominantly ethnic minority families. Two hundred and twenty-nine primary caregivers and their pre-school children were recruited from Head Start programmes in New York and New Jersey. Caregivers gave their consent to the study, completed a series of paper and pencil questionnaires, and had both their height and weight and their children’s height and weight measured. Higher availability, accessibility, and parental modelling were associated with higher consumption of fruit and vegetables in children. Availability and Accessibility were the best predictors, but Parental Modelling significantly enhanced prediction over the other variables. Public health interventions should be geared toward helping poorer families increase the availability of fruit and vegetables in their homes, advising parents on how to make them accessible, and encouraging parents to model their consumption. FUNDING: RLG receives research funding from Covidien.